PROSPECTS CULTIVATED CONIFEROUS ON THE TERRITORY STATE ARBORETUMS OF THE IVANO-FRANKIVSK REGION - Yatsyk, R. M.; Yunyk, T. R.; Shtohryn, A. S. (Forestry and Forest Melioration, 2018)
Introduction Effective introduction of alien tree species into forest cultivation requires their initial testing and assessment of growth characteristics as well as the studies of development, sustainability, perspectiveness for specific mountain conditions of Carpathian region. The regional scientific literature shows the characteristics of certain exotic species and fragmentary estimated species diversity in the arboretums. But these are not enough to make grounded scientific and practical solutions. Up to now, comprehensive description of cultivated exotic coniferous species, especially of their growth and development, remained unclear. Despite the urgency, the range of issues related to the study of ecological plasticity, adaptability and prospects of alien species for a creation of plantations of different purpose also remains unexplored in the region. First of all, it is important for improving productivity and sustainability of forest stands in the mountains, where dieback of native species occurs as well as their damage caused by diseases and pests. Materials and Methods The objects of research were cultivated coniferous plantations of “Vysokohirnyy” and “Dibrova” arboretums in Ivano-Frankivsk. Taxonomy of plants, their winter hardiness, resistance to damage and diseases, reproductive ability, decorative properties, growing capacity category status and overall prospects were estimated. Also, the qualitative assessment of plants was given by crown density, stem straightness, natural pruning, and by the ratio of solid volume to stacked volume. The data was processed by variation statistics. Dispersion and correlational analysis of the data was done. Results The exotic species were studied on the territory of the protected objects - the largest state arboretums on the Northeastern megaslope of the Ukrainian Carpathians, “Vysokohirnyy” and “Dibrova”. The presence and taxonomic structure of the species, ecotypes, and forms were determined and their current status, parameters of growth, development, resistance, quality, decorative value and overall prospects for use in plantations of different purpose were investigated. The mean annual height and diameter growth indices of the introduced species were estimated during ontogeny. The dynamics of seasonal growth, potential plants reproducibility and correlations between resistance and seed production were investigated. A comparative assessment of bio-ecological features of adaptation for the exotic species was done at different hypsometric levels of growth. Conclusions In the “Vysokohirnyy” arboretum, there are 14,069 exotic gymnospermous plants, which belong to 62 species and forms, 9 genera and 3 families. From them, the pine family accounts for 51 species, 5 genera. In “Dibrova” arboretum, there are 4,581 gymnospermous plants; they belong to 60 species and forms, 7 genera and 2 families. The pine family hire includes 57 species, 6 genera. The most prospective species for medium and high mountain forestry were: Larix laricina (Du Roi) C. Koch, L. decidua ? L. kaempferi, L. kaempferi (Lamb.) Carriere, (Picea sitchensis (Bong.) Carriere, Pseudotsuga menziesii (Mirb.) Franco, Abies nordmanniana (Steven) Spach and A. balsamea (L.) Mill. For foothills and lowland, Larix decidua L., L. polonica (Racib.), L. kaempferi (Lamb.), Pseudotsuga menziesii (Mirb.) Franco, and Pinus pallasiana D. Don were the most promising.